The relationship between the purpose in life and general health in Veterans and ordinary people - M. Mahbobi; E. Khorasani; M. etemadi; Kh. Shahidi; Zh. Khaniabad (Afarand Scholarly Publishing Institute, 2013)
Background: Purpose and meaning of life is most important issues of religious, administrative, philosophical and psychological. Having meaning and purpose in life indicate mental health and cause to increase ability to do things. Purpose: This research aimed to study relationship between the purpose in life and general health in Veterans and ordinary people. Method & Materials: This descriptive correlation study was conducted from March until June 2012. Two groups of population including veterans (154 people) and ordinary people (145 people) that all the veterans were randomly selected in the city area and Gilangharb and Seryal Zahab in Kermanshah province. Research tools were two questionnaires of Krambaf purpose in life (PIL) and General Health Questionnaire (GHQ) Goldberg. date were analyzed using SPSS software, descriptive statistics and spearman correlation and variance analyze test. Results: In this study, the mean score of purpose in life of veterans (81 ± 11.85) was higher than the ordinary people (8.45 ± 76), But the mean score of general health in ordinary people (47.47 ± 9.87) was higher than the veterans (40.12 ± 7.57) .The relationship between the score of purpose in life and general health was statistically significant that this relationship was higher in ordinary people (r=0.61, p<0.001). Conclusion: In this study, life expectancy and general health status in veterans is higher than ordinary people. General health status in both groups is higher than the cut-off point so we require the serious attention of policy makers to improve public health.